Increasing Brain Permeability of PHA-767491, a Cell Division Cycle 7 Kinase Inhibitor, with Biodegradable Polymeric Nanoparticles - Elisa Rojas-Prats; Carlota Tosat-Bitrián; Loreto Martínez-González; Vanesa Nozal; Daniel I. Pérez; Ana Martínez (MDPI AG, 2021)
A potent cell division cycle 7 (CDC7) kinase inhibitor, known as PHA-767491, has been described to reduce the transactive response DNA binding protein of 43 KDa (TDP-43) phosphorylation in vitro and in vivo, which is one of the main proteins found to aggregate and accumulate in the cytoplasm of motoneurons in amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD) patients. However, the main drawback of this compound is its low permeability to the central nervous system (CNS), limiting its use for the treatment of neurological conditions. In this context, the use of drug delivery systems like nanocarriers has become an interesting approach to improve drug release to the CNS. In this study, we prepared and characterized biodegradable nanoparticles in order to encapsulate PHA-767491 and improve its permeability to the CNS. Our results demonstrate that poly (lactic-co-glycolic acid) (PLGA) nanoparticles with an average radius between 145 and 155 nm could be used to entrap PHA-767491 and enhance the permeability of this compound through the blood-brain barrier (BBB), becoming a promising candidate for the treatment of TDP-43 proteinopathies such as ALS.